Post-transplant immunosuppression: regulation of the efflux of allospecific effector T cells from lymphoid tissues. - David J Swan; John A Kirby; Simi Ali (PLoS ONE, 2012)
A functional sphingosine-1-phosphate (S1P) receptor antagonist specifically inhibited the egress of activated allospecific T cells from draining popliteal lymph nodes in alloantigen-sensitised mice. The level of S1P receptor 1 (S1PR1) mRNA was similarly reduced 1 and 3 days after mitogenic activation of T cells. However, the response of these cells to the S1PR1-specific agonist SEW2871 was only reduced on the first day after T cell activation with normal receptor-mediated Akt-phosphorylation restored by day 3. Longitudinal analysis of CD69 expression showed that almost all T cells expressed this antigen on days 1 and 3 after activation. However, the absolute level of cell-surface expression of CD69 peaked on undivided T cells and was then halved by each of the first 3 cycles of mitosis. CD69-specific small interfering RNA (siRNA) reduced the maximal level of CD69 expression by undivided, mitogen-stimulated T cells. These cells retained their capacity to phosphorylate Akt in response to stimulation with SEW2871. These data show that S1P receptors are involved in controlling the egress of activated T cells from lymph nodes, and that S1PR1 function is regulated by the level of T cell surface CD69. They suggest a potential for augmentation of this process to deplete alloreactive effector cells after organ transplantation.